PERAN MAHASISWA KKN IAKN TARUTUNG DALAM KEGIATAN SOSIAL KEMASYARAKATAN DESA BELANG MALUM SIDIKKALANG - Santiana Hutahaean; Sudung Hutagalung; Evelin Sihombing; Ingrit Nababan; Dicky Sinaga (Universitas Persada Indonesia YAI, 2026)
One application of the Tri Dharma of Higher Education is the Community Service Program(Kuliah Kerja Nyata or KKN). It gives students the chance to put their academic knowledge touse in practical situations while also acting as a community participation program. The purposeof this study is to investigate how students from the Indonesian Christian Institute of Tarutung(IAKN Tarutung) participate in social and community activities in Belang Malum Village,Sidikalang District, Dairi Regency, as part of the Community Service Program (KKN). Datafor this study was gathered through observation, interviews, and recording using adescriptive qualitative methodology. An interactive analytical approach that included datareduction, data display, and conclusion drawing was used to examine the data. The resultsshow that KKN students actively participated in village development through communityservice projects, support for village government services, health and education programs,the Minggu Ceria program, and community empowerment projects like the creation offamily medicinal plant gardens and flower gardens. Every program was carried out using aparticipative approach, enhancing cooperation between the local community, villagegovernment, and university. In addition to helping the community, the KKN programimproved students' social awareness, leadership, communication, and academic proficiency.As a result, KKN is a useful tool for promoting sustainable rural development and fortifyinguniversity-community ties. Keywords: Community Engagement; Community Service Program;Rural Development; Social Activities; Student Role.